Public Opinion Polling in a Globalized World - Carballo, Marita; Hjelmar, Ulf.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Understanding public opinion is integral to modern democracies. It shapes public policies; it helps politicians to connect with their audiences; it reveals underlying issues that are of utmost importance for political decision-makers. Social research and opinion polls give people the opportunity to express their views regularly on different topics and provide an efficient way to measure public opinion. The purpose of this book is to illustrate how public opinion polling matters in politics, in the public sphere and more generally in our globalized economies. The book provides an international and up to date perspecive on public opinion polling. It is based on studies from more than 50 countries across the world and in-depth case studies from the United States; Canada, Germany, Great Britain, France, Norway, the Western Balkans, India, Indonesia, New Zealand and the Philippines.
International Polls -- The Effects of Globalisation on the Perception of Democracy -- Transatlantic Trends: Convergences and Divergences -- A Europe of Values: From Shared History to Common Objectives -- Latin America$1 (Bs Mixed Views About Globalization, Investments and the United States -- How Do the Western Balkans See Their Future? -- Public Opinion Polling in National Elections -- Exit Polls $1 (BA Lot More than Just a Tool for Election Forecasts -- Methodological Issues in Pre-Election Polling: Lessons from ABC News$1 (B32-Night Tracking Poll -- The Presidential Elections in France 2007 $1 (BThe Role of Opinion Polls -- Voters Lack Commitment: Canada -- The Public Sector in Transition -- Developing Employment Policy in Europe -- The School Sport Partnership Programme $1 (BRaising Levels of Participation in Physical Education and Sport in Schools in England -- Client Satisfaction with Public Services: A Norwegian Case -- Asia on the Move -- The Role of Social Research in Development Programs: Examples from India -- A Framework for Social Development Assessment -- Polling in Developing Democracies $1 (BThe Case of the Philippines -- M?ori Television Services $1 (BRaising Knowledge of M?ori Language and Culture in New Zealand.s
Keywords: Business; Marketing; Management; Political science; Statistics; Economics; Management science; Sociology; Business and Management; Marketing; Management; Sociology, general; Political Science; Statistics for Social Science, Behavorial Science, Education, Public Policy, and Law; Economics, general; Electronic books